(untitled) (Research, Society and Development, 2022)
Artisanal gold mining is a worldwide activity that includes about 20 million prospectors and produces up to 450 tons/year of mercury. Mercury is the main reagent for gold extraction in artisanal explorations, but its misuse can contaminate the environment. Unlike mercury, cyanide (CN) can be volatile and pose no risk of environmental accumulation. New technologies are being researched for the eradication of mercury in mining, and to produce "green cyanide" of natural origin from cassava to replace the use of mercury in mining, this contains glycosides that generate cyanide and that can be used to leach gold (melt the gold), transforming it into the ionic form for later recovery with the use of activated carbon and electrolysis. The objective of this study was to show the distribution of cassava production in Brazil, to briefly consider the products generated and to present their potential in the regional use of Amazonas, for this purpose, a search for data on cassava productivity in Brazil in repositories of public bodies was carried out. officials, compiled the data and presented the results, with the main conclusions being that: It is possible to find abundant cyanogenic products in (stem, leaves and roots) of cassava – an edible plant from the Amazon, and generate from 111 to 334 thousand tons of CN -, New economic models can help to synthesize products with high added technological value in the cassava industry or agribusiness and generate income for the Amazonians, mainly for the Amazonians.